Policy-Driven Hybrid Work and Employee Well-Being in the Public Sector: The Moderating Role of Job Autonomy - Roswiyanti; Dyan Fauziah Suryadi; Sukri; Lukman (Global Research Collaboration, 2026)
The psychological well-being of civil servants has emerged as a critical concern in post-pandemic public sector human resource management, particularly amid the institutionalization of hybrid work arrangements through government regulation. This study investigates the effect of policy-driven hybrid work on employee well-being among civil servants (Aparatur Sipil Negara) in Kota Palopo, Indonesia, and examines the moderating role of job autonomy in this relationship. Grounded in the Job Demands–Resources (JD-R) Model, Self-Determination Theory (SDT), and Conservation of Resources (COR) Theory, the study employs a quantitative cross-sectional design with respondents selected through proportionate stratified random sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. Results confirm that policy-driven hybrid work positively and significantly affects employee well-being, and that job autonomy significantly moderates this relationship, amplifying well-being outcomes among civil servants with higher autonomy. These findings advance JD-R theory by conceptualizing job autonomy as a conversion resource that determines how effectively state-mandated hybrid work arrangements translate into employee psychological well-being, with important implications for hybrid work policy design in non-Western public bureaucracies.